Treating equals equally and unequals unequally in one-sided matching markets - Cantala, David; Mendoza-Palacios, Saul (Estudios Económicos de El Colegio de México, 2025)
We introduce in the one-sided assignment game by Shapley and Scarf (1974) the requirement called “Treating equals equally and unequal unequally” (TEEUU). We model an assignment as a measurable function that assigns a type of good to each type of agent. We establish: 1) a method, originated in optimal transportation theory, to find a TEEUU assignment in the core whenever it exists- by searching a Pareto optimal assignment- and 2) conditions under which a TEEUU assignment in the core always exists.